1974
DOI: 10.1530/jrf.0.0380091
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of the Male Preputial Gland to the Acceleration of Oestrus in the Laboratory Mouse

Abstract: The effect of the male preputial gland on the oestrous cycle in mice was investigated. Urine from preputialectomized (but otherwise intact) males was slightly but not significantly more effective in stimulating oestrus than urine from castrates, but it was significantly less effective than urine from intact males. Preputialectomized males inseminated fewer females with a less pronounced Day-3 peak of inseminations than intact males. It is concluded that the preputial secretion is at least partly responsible fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1976
1976
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Sexual behavior could be affected in Mab21l1 -/-mice for either of the following reasons. First, the preputial gland in male mice has been shown to contribute to pheromonal function: generating chemosignals that attract females and accelerating oestrus (Bronson and Caroom, 1971;Chipman and Albrecht, 1974). Second, the localization of Mab21l1 transcripts within the CNS is consistent with studies that link reproductive behavior to specific regions of the brain, collectively known as the vomeronasal system (VNS) (Segovia Mab21l1 in lens placode development and Guillamon, 1993).…”
Section: Male and Female Sterility In Mab21l1 Mutantsmentioning
confidence: 65%
“…Sexual behavior could be affected in Mab21l1 -/-mice for either of the following reasons. First, the preputial gland in male mice has been shown to contribute to pheromonal function: generating chemosignals that attract females and accelerating oestrus (Bronson and Caroom, 1971;Chipman and Albrecht, 1974). Second, the localization of Mab21l1 transcripts within the CNS is consistent with studies that link reproductive behavior to specific regions of the brain, collectively known as the vomeronasal system (VNS) (Segovia Mab21l1 in lens placode development and Guillamon, 1993).…”
Section: Male and Female Sterility In Mab21l1 Mutantsmentioning
confidence: 65%
“…Whether or not the farnesene^MUP complex is assembled already in the preputial secretion or in the voided urine is currently unknown. Importantly, the fact that both the farnesenes and the bladder-originated volatile ligands are active in puberty acceleration could help resolve yet another long-term controversy in the literature pertaining to a source of the oestrus-inducing chemosignal (Chipman & Albrecht 1974;). We have previously found that a mixture of BT with DB in water (Jemiolo et al 1986) and a mixture of a-and b-farnesene (Ma et al 1999) are both active in oestrus induction.…”
Section: Discussionmentioning
confidence: 99%
“…C hipman and Albrecht [1974] have suggested that the secretion can accel erate the estrous cycle in the mouse.…”
Section: Discussionmentioning
confidence: 99%